The Impact Of Downstream Policies On The Growth Of Indonesia's Net Exports Of Iron And Steel (HS 72) - Khadijah Mahani; Ignatia Martha Hendrati; Wirya Wardaya (UNIVED Press, 2025)
This study examines the impact of downstream policies on Indonesia's net exports of iron and steel (HS 72) during 2000–2023. The downstream policy, aimed at enhancing value-added and reducing raw material exports, is crucial for improving trade balances and boosting economic growth. Using paired t-tests and Export Product Dynamics (EPD), the study reveals significant increases in total exports (5%, 0.041) and total imports (1%, 0.001), while net export improvements were marginally significant (10%, 0.08). Despite the positive impacts, challenges such as high dependency on imported raw materials and the need for substantial infrastructure investments persist.